PENGALAMAN IBU YANG MEMILIKI ANAK USIA PRASEKOLAH KESULITAN MAKAN DI PAUD IMANUEL PEKANBARU; STUDI FENOMENOLOGI - Raja Fitrina Lestari; Afrila Bella Sari; Meisa Daniati (LPPM Universitas Muhammadiyah Riau, 2017)
Feeding problem is one of problems in preschool who is complained by parents. This research means to acquire the significance experience of mother who has feeding problem child at preschool. This research was conducted through qualitative approach to the design of phenomenology. The methods of data collection are interview and observation. The participants of this research are five mothers of Imanuel PAUD Pekanbaru. The data is processed in verbatim form, and then analyzed by Collaizy technique. This research identified of two themes, namely are: the influence factor of feeding problem, psychologist factor and food rule; the manner of overcome feeding problem are the effort feeding, seduce, giving love, lure and follow the wishes of children. From this research, participant show their children difficulty to eat look from physicologic factor and food setting factor. The way to accoplish difficulty eating who done by participant with possitive way are: follow their child eat together, give love and give attention. While the negative way are: follow their wish of child, feed, tantalize, and force the child to eat. The result of this research expect to be reading material and guideline for parents in dealing feeding problem in children. So preschooler achieve optimal growth.